Inattention symptom severity and cognitive processes in children at risk of ADHD: the moderating role of separation anxiety - Anning, Kate L.; Langley, Kate; Hobson, Christopher; De Sonneville, Leo; Van Goozen, Stephanie H.M. (Child neuropsychology, 2024)
Impairments in cognitive processes and their associations with dimensional measures of inattention, hyperactivity-impulsivity and anxiety were examined in children at risk of Attention-Deficit Hyperactivity Disorder. Children referred by teachers for exhibiting ADHD-type problems (n = 116; 43 meeting full diagnostic criteria for ADHD; 4-8 years) completed computerized tasks measuring episodic memory, response inhibition, visuomotor control and sustained attention, while parents were interviewed (DAWBA) to assess ADHD and anxiety symptoms. Of the 116 children assessed, 72% exhibited impaired cognitive processes; 47% had impaired visuomotor control, 37% impaired response inhibition, and 35% had impaired episodic memory. Correlational and hierarchical regression analyses using our final analytic sample (i.e., children who completed all cognitive tasks and a vocabulary assessment, n = 114) showed that poorer task performance and greater within-subject variability were significantly associated with more severe inattention symptoms but not with hyperactivity-impulsivity severity. Symptoms of separation anxiety, which were reported in over half of the sample, moderated associations between inattention and episodic memory, and between inattention and inhibition. Only children without separation anxiety showed significant correlations between ADHD symptoms and poor performance. However, separation anxiety had no moderating effect on associations between inattention and visuomotor control or sustaining attention. Children exhibiting signs of ADHD show impairments across a range of cognitive tasks. Further research to improve our understanding of these processes may be useful in the development of early interventions. Our results suggest that separation anxiety should be taken into account when considering interventions to address emerging neuropsychological deficits associated with this disorder.